Шетел азаматтарының Қазақстан Республикасы балаларын асырап алудың ерекшеліктері мен құқықтық салдары - Асильбекова, Г.А.; Абдрашева, Т.М. (My University, 2011)
В статье изучены основы, правовые последствия усыновления иностранцами детей Республики Казахстан. Приведено общее число детей-сирот в республике, число лиц, изъявивших желание усыновить, а также число детей, взятых за рубежом на консульский учет в 2005–2009 гг. Коренным образом раскрыты требования законодательства Республики Казахстан, предъявляемые к лицам, изъявившим желание усыновить ребенка. Представлены эффективные пути и способы уменьшения числа детей сирот. Изучены международные Конвенции и законодательные акты Республики Казахстан, регулирующие вопросы усыновления. In this article learnt the basics (principles) and the legal effect of adoptions of the Kazakhstan by foreigners. Made a generalization to the total number of orphans in the Republic of Kazakhstan, the number of persons wishing to adopt, as well as the number of children taken abroad for the consulate in 2005–2009 years. Radically opened all legal requirements of the Republic of Kazakhstan are presents for persons who have desire to adopt. The article presents effective ways and means to reduce the number of orphans. There were studied International Conventions and laws of the Republic of Kazakhstan governing adoptions.
Keywords: Неке жəне отбасы; Бала асырап алу туралы Заң; Шетелдік азаматтар; ҚР